2008
DOI: 10.1126/science.1164759
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Identification of Carbonate-Bearing Rocks on Mars

Abstract: Geochemical models for Mars predict carbonate formation during aqueous alteration. Carbonate-bearing rocks had not previously been detected on Mars' surface, but Mars Reconnaissance Orbiter mapping reveals a regional rock layer with near-infrared spectral characteristics that are consistent with the presence of magnesium carbonate in the Nili Fossae region. The carbonate is closely associated with both phyllosilicate-bearing and olivine-rich rock units and probably formed during the Noachian or early Hesperian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
554
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 585 publications
(603 citation statements)
references
References 33 publications
(10 reference statements)
28
554
2
5
Order By: Relevance
“…It now seems clear that carbonates do not exist as extensive, thick, laterally continuous bedrock units on the surface of the planet similar to those on Earth. Instead local deposits of carbonate have been discovered Ehlmann et al 2008b;Morris et al 2010), with the possibility of additional discoveries at smaller spatial scales or in mixed units excavated from the subsurface (Michalski and Niles 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It now seems clear that carbonates do not exist as extensive, thick, laterally continuous bedrock units on the surface of the planet similar to those on Earth. Instead local deposits of carbonate have been discovered Ehlmann et al 2008b;Morris et al 2010), with the possibility of additional discoveries at smaller spatial scales or in mixed units excavated from the subsurface (Michalski and Niles 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They would also explain particular mixtures of clays and evaporites observed in specific localities: phyllosilicates and evaporites appear sometimes within meters or even in spatial juxtaposition of each other. This has been shown by the MER Spirit in the Columbia Hills at Gusev crater [ Wang et al ., 2006], by the MER Opportunity on the rim of Endeavour crater at Meridiani Planum [ Arvidson et al ., 2014], by the MSL Curiosity in Yellowknife Bay at Gale crater [ Vaniman et al ., 2014], and by MEX鈥怬MEGA and MRO鈥怌RISM in several places on Mars, including regional coexposures of phyllosilicates with either carbonates [ Ehlmann et al ., 2008, 2011; Carter and Poulet , 2012], sulfates [ Poulet et al ., 2005; Wiseman et al ., 2008; Hamilton et al ., 2008; Murchie et al ., 2009; Wray et al ., 2009; Milliken et al ., 2014], or chlorides [ Murchie et al ., 2009] in different locations, and even the presence of sulfate鈥恇earing materials underlying phyllosilicate鈥恇earing strata [ Wray et al ., 2010]. …”
Section: Discussionmentioning
confidence: 99%
“…Provided the existence of an alternative source of anions, mainly derived from volcanic volatiles [ Halevy and Head , 2014], it is expected that these ions would have bonded in evaporites (i.e., sulfates). However, in most localities on Mars, evaporites are commonly absent in clay鈥恉ominated sediments [ Bandfield et al ., 2003; Bishop et al ., 2008; Ehlmann et al ., 2008; Osterloo et al ., 2008]. As a particular example, evaporites in Gale crater are the result of postdepositional fluid migration, in different late鈥恠tage episodes of fluid flow; therefore, clays and evaporites at Gale have very different depositional histories, occurring spatially closely but with deposition times separated by hundreds of millions of years [ Nachon et al ., 2014; Rapin et al ., 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Mg-carbonates are highly undersaturated in our experiments (W $ 10 脌5 ), but would likely form in special environments [Ehlmann et al, 2008]. More sulfates would form later in Mars' history as older sulfites were exposed to the oxidizing atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…To address this we conducted a series of mineral precipitation experiments from O 2 -poor solutions saturated with both calcite and hannebachite and found that inhibition of carbonate precipitation occurs at even lower values of pSO 2 :pCO 2 than predicted. This implies that even if SO 2 were not abundant enough to influence Noachian climate, it may provide an explanation for the scarcity of carbonate minerals at outcrop abundance [Christensen et al, 2001], other than in laterally restricted environments that may not represent prevailing early Martian surface conditions [Ehlmann et al, 2008]. Because this explanation for the scarcity of carbonates does not require acidic conditions, it may also account for the occurrence of early phyllosilicates [Poulet et al, 2005], which require near-neutral pH to form [Velde, 1995].…”
Section: Introductionmentioning
confidence: 99%